Analisis Komparatif Pemikiran Imam Al-Ghazali Tentang Konsep Teori Produksi - Andi Fika Widuri; Udin Saripudin (Al Maal: Journal of Islamic Economics and Banking, 2022)
Today, production problems are complex. The majority of production activities lead to unmoral judgment. This condition is dominated by the thinking of a capitalist and socialist economic system. The focus of the production theory of Muslim thinkers studied is Al-Ghazali, but it is juxtaposed with the perspectives of other Muslim thinkers, namely Ibn Khaldun, Muhammad Baqir Al-Sadr and Muhammad Abdul Mannan in order to complete and provide solutions to current production problems. This research is library research. using a sociological-historical approach. The method of data collection in this study used the documentation method. Then analyzed using comparative descriptive analysis. The results showed that al-Ghazali's perspective with other Muslim thinkers had two tendencies, namely similarities and differences. From the equation side, it consists of the definition of production; production purposes; the view of production in Islam; factor; and cooperation in production. Meanwhile, in terms of differences, there are 2 aspects, namely competition in production and levels in production